Life Skill Education And Adolescent Reproductive Sexual Health Kalinga Institute of Social Sciencesi(KISS) An Experimental Hub For Tribal Student. - Murmu (Research Scholar), Raghunath; Acharya (Lecturer in Education), Sunita (International Journal of Psychosocial Rehabilitation, 2020)
Present study intends to study regarding life skill education and reproductive sexual health education implementing at KISS which is the long-term strategic interventions to improve tribal adolescent better health, education and nutrition. Many studies conducted on life skill and health education of tribal adolescents give an insight into the strategic implications of reaching the adolescent girls effectively. In the same time the primary objectives for undertaking this study are to understand the concept of LSE and ARSH among the tribal adolescents, to assess three knowledge, attitude and practice on ARSH among the tribal adolescents those are taking training at KISS for their sustainable development. We conducted the study in within KISS which is one of the best tribal dominated organizations of Odisha in particular in the world in general recognized by international organisation like UNO. To provide justification to the present title we have taken three issues as research question upon which the further discussion based on along with same number of objectives. In this study we have taken 100 tribal students from the organisation. For collection of data from them researchers used structured self-standardised questionnaire along with interview schedule focussing different issues relating reproductive sexual health and life skill education. Here study found that both the programme successfully implementing there have incomparable benefits for tribal girls in particular students in general. At least some suggestions were made like before initiating any interventions related to ARSH and life skills for students there should be intervention program to orient concerned resource persons along with all other staff those are in the field of implementation.